Formaldehyde - free crosslinker synthesis in waterborne binder dispersions for textile industry - Aracı, Seda. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
In textile industry, the binders used are mostly water based acrylic dispersions. These binders provide strength, elastic recovery, soft hand, flexibility, color retention and also resistance to washing and aging to the textile and nonwoven. Nevertheless, binders having no reactive functional monomers are not very successful in imparting these properties. Self crosslinking monomers are used to improve the properties of textile and non woven end products. N-methylolacrylamide (NMA) is one of these monomers having functional groups for self-crosslinking. However, N-methylol acrylamide used in textile binders emit formaldehyde during crosslinking at high temperatures. This formaldehyde either remains in the end product or is liberated into the air. The U.S. Department of Health and Human Services published the 12th Report on Carcinogens and formaldehyde is listed in the category of known to be a human carcinogen. Researchers on textile sector are focud on the subject of formaldehyde emission due to the harmfull effects on both people and environment. In this study, a novel monomer that emmits no formaldehyde and have ability to self-crosslink was investigated for replacement of NMA and the performance results are compared with that of NMA.
Keywords: Coatings.; Emulsion paint.